The disjuncture of learning and recognition: Licensure-related credential assessment from the standpoint of Chinese immigrant engineers in Canada - Hongxia Shan (Adult Education Research Conference, 2012)
Non/recognition of foreign credentials has been criticized for obstructing skilled immigrants from succeeding in the Canadian labour market. Despite the criticisms, rarely is empirical investigation conducted to pin down the gaps and contradictions in specific assessment mechanisms. This paper is an effort to this end. Drawing on an institutional ethnographic study of the credential assessment practices in the engineering profession, the study problematizes the redundant and ad hoc assessment procedures, licensure bodies‘ narrow focus on applicants‘ undergraduate education, and their deficit approach to training from other countries.